Exploring store image and green trust as predictors of food store loyalty: A structural model from an emerging market - Bui Van Quang; Nguyen Thi Van (Journal of Open Innovation: Technology, Market and Complexity, 2025)
This study investigates the influence of store image attributes and consumer green food trust in customer satisfaction and store loyalty within the context of Vietnam's emerging food market. Grounded in the Commitment-Trust Theory, the Open Innovation Dynamics Theory and the Theory of Planned Behavior, the research develops and tests an integrated model that incorporates essential dimensions of store image—specifically, product assortment, store environment, sales service, and temporal aspects—alongside consumer trust in green food. Data were collected through a structured questionnaire administered to a sample of 386 consumers in Ho Chi Minh City, and the results were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that product assortment, sales service, and trust in green food significantly impact customer satisfaction and loyalty, with customer satisfaction as a vital mediating variable. In contrast, the store environment and temporal aspects did not directly affect store loyalty significantly. These results indicate a consumer trend toward prioritizing functional and health-related factors over atmospheric or convenience-related elements in food retail settings. This study contributes to the existing literature by applying established behavioral theories within a transitional market. It offers strategic insights for retailers seeking to enhance customer loyalty through trust-building and value-oriented offerings in the green food sector.